Ethno-nationalism and impediments to cooperation in tourism in a post-settlement Cyprus?. Issue 2 (12th September 2016) - Webster, Craig; Jacobson, David; Shapiro, Kelsey
Abstract : Purpose: The purpose of this paper is to clarify the position of Greek Cypriot and Turkish Cypriot professionals in the hotel and tourism industry on the island of Cyprus with regards to their expectations regarding the benefit of a political solution to the Cyprus problem on the island. Design/methodology/approach: The paper uses data from two surveys in both political entities of the island. One survey is a survey of hotel owners, managers of hotels and travel agencies in both political entities on the island. The other is semi-structured interview with leading professionals in the hospitality and tourism industry in both political entities. Findings: The surveys indicate that there is an expectation from professionals in both entities that tourism will benefit all following a solution, with large increases in incoming tourism to Cyprus. Practical implications: The findings indicate that there are substantial expectations that there will be benefits for all following a solution to the Cyprus problem. Originality/value: This is a first future-oriented paper regarding the expectations of major players in the hotel and tourism industry in both political entities on the island.